Investigation and Analysis of the Simultaneous Switching Noise in Power Distribution Network with Multi-Power Supplies of High Speed CMOS Circuits - Khaoula Ait Belaid; Hassan Belahrach; Hassan Ayad (Active and Passive Electronic Components)
The paper studies a simultaneous switching noise (SSN) in a power distribution network (PDN) with dual supply voltages and two cores. This is achieved by reducing the admittance matrix Y of the PDN then calculating frequency domain impedance with rational function approximation using vector fitting. This paper presents a method of computing the simultaneous switching noise through a switching current, whose properties and details are described. Thus, the results are discussed and performed using MATLAB and PSpice tools. It demonstrated that the presence of many cores in the same PCB influences the SSN due to electromagnetic coupling.